Symposium 5: Applications of networked learning to the support of learning and teaching in higher education - Kehrwald, Benjamin A.; Chanane, Nawal; Eberhard, Sally; Nguyen, Nhung; Sim, Kwong Nui; Winters, Annemie (Proceedings of the International Conference on Networked Learning, 2024)
This symposium is the result of a broad effort by the authors to consider the applicability of networked learning to our work to support learning and teaching across our institution. We, the authors, work in a central learning and teaching support unit within Auckland University of Technology (AUT), in Auckland, Aotearoa/New Zealand. We are concerned with how networked learning is applicable to our efforts to support learning and teaching at AUT-specifically- to operationalise the institution’s strategic commitments to learner success. Our focus on supporting learning and teaching operates at various levels, from the ‘local’ level of individual courses to the intermediate level of supporting degree programmes to the more ‘global’ level associated with developing institutional policy that supports effective academic teaching practices and the ongoing evolution of a technology infrastructure that enables and supports productive learning and teaching activity. Moreover, our work deals with questions and challenges which range from specific, situated practical challenges to broad, philosophical questions which affect learning and teaching across the institution. This symposium represents our efforts to synthesise our understandings of networked learning and connect general ideas about networked learning with specific, situated aspects of our work to support learning and teaching across the institution.